Activity Ratio and Profitability Ratio Analysis to Know Causes of Decreasing Profit: Case Study at the Village Credit Institution of the Suwat Village - Dewa Ayu Mirah Sri Devi; I Ketut Sudiartha; I Gede Made Karma (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
The Village Credit Institution (LPD) of DesaPakramanSuwat has productive assets in the form of loans provided to the community. The loan disbursed fluctuated from 2019-2021. Based on the report on activities and credit developments at the PakramanSuwat Village LPD, the loans granted in 2019-2021 are fully eligible for current collectibility. However, this is not in line with the development of LPD profits which have decreased in 2020 and 2021.This study aims to analyze the causes of the decline in LPD profits in terms of credit turnover, BOPO, net profit margin, return on equity, and return on assets. The type of research used in this research is descriptive research with a qualitative approach. The analysis techniques in this research are activity ratio analysis, profitability ratio analysis, and trend analysis.The results of this study indicate that the level of LPD activity in PakramanSuwat Village has decreased which can be seen based on the credit turnover which has decreased from 2019-2021. The decrease in credit turnover was caused by a small amount of collectible loans so that loan interest income decreased so that it affected the decline in LPD profitability. The level of profitability of the LPD PakramanSuwat Village also experienced a decrease which can be seen from the BOPO ratio and the decline in the ratio of NPM, ROE, and ROA. This decrease in profitability was due to operating expenses, decreased operating income, decreased other operating income, the company's capital being not managed optimally, and the company's assets being not managed optimally